Dampak Revolusi Mobilisasi Penduduk terhadap Persebaran Penyakit Menular di Indonesia - Oktavia Beni Kujariningrum; Anisa Nur Cahyanti; Rofifatun Nisa; Farid Agushybana; Sri Winarni; Cahya Tri Purnami (Universitas Widya Gama Mahakam Samarinda, 2021)
Background: Increased population mobility has continued to occur over time, especially worker mobility consisting of commuter mobility and circular mobility. A person's mobility is very influential on the condition of health status, especially related to the spread of infectious diseases. Direct infectious disease is a disease with the transfer of germs through physical contact from a sick person or a carrier to a healthy person. Objectives: To analyze the impact of the population mobility revolution on the spread of infectious diseases in Indonesia. Research Metodes: The study was conducted by studying literature through collecting supporting articles and analyzing secondary data. The data used are direct infectious disease data consisting of Tuberculosis, HIV, Hepatitis and Leprosy from the Indonesian Health Profile, Main Results of Basic Health Research, and Statistics Data from the Central Statistics Agency, as well as previous research articles. Results: The trend of the mobility of movers experienced an increase in line with trends in communicable diseases such as Tuberculosis, HIV, and Hepatitis. High mobility affects the spread of infectious diseases Tuberculosis, Hepatitis and Leprosy seen from the factor of interaction with others, as well as the influence on HIV. The influence can be seen from Commercial Sex Workers (CSWs) who transmit to their customers and the families of CSW customers who can transmit it to their wives. Conclusion: The increased mobility pattern of movers is accompanied by an increased pattern of direct infectious diseases including tuberculosis, HIV, and hepatitis.